A numerical model for wave-current interaction at the scale of marine engineering. (12th February 2016) - Lalli, F.; Bruschi, A.; Cassese, M.L.; Lotti, A.; Pesarino, V.
ABSTRACT: In the present paper a numerical method for marine and coastal hydrodynamics is presented. It aims at developing a formulation for the complete wave-current coupling in the time domain. In this framework, both waves and currents are handled by complete Navier–Stokes equations. Indeed, waves are modified by currents and interaction with structures, the flow is forced by waves and structures as well. The numerical solution for fully 3D equations is outlined, showing that the proposed procedure is a revisited version of the fractional step method, i.e. the free surface fractional step method. Some numerical test cases in simple 2D geometries (vertical direction vs direction of wave propagation) are shown.